How Country Image Affects Intention to Visit a Destination: Evidence from Russian Tourists Visiting Switzerland - PONNAPUREDDY, Sindhuri; WAGENSEIL, Urs; BELOZEROVA, Oxana; MIRZOIAN, Siuzanna (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018, 2018)
The paper examines how country image affects the intention to visit a destination by means of a quantitative study conducted in Russia. It specifically explores the mediating influence of psychological destination image, functional destination image, and attitude towards the destination between country image and visiting intention. Data for the research were collected from a survey involving 919 respondents in Russia who had gone on a vacation, at least, once in the past 12 months. A series of mediation models indicated that through psychological destination image, functional destination image, and attitude towards the destination, country image mediates the intention to visit. The results imply that the holistic brand image of a destination has a strong influence on international tourists’ intention to visit. Therefore, marketers should integrate country image in destination marketing messages.